Advances in transcatheter mitral and tricuspid therapies - Pavel Overtchouk; Nicolo Piazza; Juan Granada; Osama Soliman; Bernard Prendergast; Thomas Modine (BMC Cardiovascular Disorders, 2020)
Abstract Background While rheumatic mitral stenosis has been effectively treated percutaneously for more than 20 years, mitral and tricuspid regurgitation treatment appear as a contemporary unmet need. The advent of transcatheter therapies offer new treatment options to often elderly and frail patients at high risk for open surgery. We aimed at providing an updated review of fast-growing domain of transcatheter mitral and tricuspid technology. Main body We reviewed the existing literature on mitral and tricuspid transcatheter therapies. Mitraclip is becoming an established therapy for secondary mitral regurgitation in selected patients with disproportionately severe regurgitation associated with moderate left ventricle dysfunction. Evidence is less convincing for primary mitral regurgitation. Transcatheter mitral valve replacement is a promising emerging alternative to transcatheter repair, for secondary as well as primary mitral regurgitation. But further development is needed to improve delivery. Transcatheter tricuspid intervention arrives late after similar technologies have been developed for aortic and mitral valves and is currently at its infancy. This is likely due in part to previously under-recognized impact of tricuspid regurgitation on patient outcomes. Edge-to-edge repair is the most advanced transcatheter solution in development. Data on tricuspid annuloplasty and replacement is limited, and more research is warranted. Conclusion The future appears bright for transcatheter mitral therapies, albeit their place in clinical practice is yet to be clearly defined. Tricuspid transcatheter therapies might address the unmet need of tricuspid regurgitation treatment.